Feasibility and reproducibility of BOLD and TOLD measurements in the liver with oxygen and carbogen gas challenge in healthy volunteers and patients with hepatocellular carcinoma. Issue 4 (28th September 2015) - Bane, Octavia; Besa, Cecilia; Wagner, Mathilde; Oesingmann, Niels; Zhu, Hongfa; Fiel, Maria Isabel; Taouli, Bachir
Abstract : Purpose: To quantify baseline relaxation rates R 2 * and R1 in the abdomen, their changes after respiratory challenges, and their reproducibility in healthy volunteers and patients with hepatocellular carcinoma (HCC) at 1.5T and 3.0T. Materials and Methods: R 2 * measurements were acquired in the liver in 8 volunteers and 27 patients with 34 HCCs using multiecho T 2 * at baseline and after respiratory challenges with 100% oxygen (O2 ) and carbogen (CB = 95%O2 /5%CO2 ). R1 was measured at 1.5T in one volunteer and 21 patients with 23 HCCs. Test–retest coefficient of variation (CV) was assessed in 10 subjects. Intra‐ and interobserver variability of R 2 * and R1 measurements was assessed in 12 and 10 patients, respectively. Parameters for HCC, liver, and muscle were compared between baseline and after gas challenges. Results: We observed that R 2 * and R1 imaging of HCCs with O2 and CB is feasible and reproducible (test–retest CV R 2 * <15%/R1 <5%; intra‐ and interobserver intraclass correlation coefficient R 2 * >0.88/R1 >0.7 and CV R 2 * <7%/R1 <3% at 1.5T). R 2 * measurements were observed to be less reproducible at 3.0T (CV<35%). There was a statistically significant decrease in R 2 * values in HCC before and after O2 ( P = 0.02) and increase in R1 after O2 ( P = 0.004). CB had no significant effect ( P R 2 * = 0.47/R1 = 0.278). Conclusion: R 2 * measurements in HCC and liver parenchyma are more reproducible at 1.5T than at 3.0T, and with O2 than with CB challenge. We observed a decrease in R 2 * and an increase in R1 of HCCs from baseline in response to O2 challenge, as expected with increased tissue and blood oxygenation. J. Magn. Reson. Imaging 2016;43:866–876